Sildenafil Affects Olfactory Function - Gudziol, V.; Mück-Weymann, Michael; Seizinger, Oliver; Rauh, Robert; Hummel, Thomas; et al. (Journal of Urology, 2007)
Purpose: Sildenafil is the first member of a new class of oral drugs effective for erectile dysfunction. However, approximately 20% of patients complain about nasal congestion after sildenafil administration. Materials and Methods: Because nasal airflow and olfaction are closely linked, the sense of smell was evaluated in 20 young, healthy volunteers after the administration of 50 and 100 mg sildenafil, and placebo in a double-blinded, crossover study. Olfactory function was evaluated using a standardized and validated test (Sniffin' Sticks®). To investigate a possible impact of G-protein β3 subunit C825T polymorphism on the effect of sildenafil on olfaction the genotype of all subjects was determined. Results: The effect of sildenafil on olfaction was only present at a dose of 100 mg but not at a dose of 50 mg sildenafil. The genotypes TT, CC and TC of the G-protein β3 C825T polymorphism had no impact on the change in olfactory function. Conclusions: Higher sildenafil doses may produce decreased olfactory sensitivity. © 2007 American Urological Association.
Created from Fastlane, Scopus look-up
Keywords: odors; penile erection; penis; sildenafil